Informações ausentes e desinformações presentes: coleção etnográfica Xikrín do Cateté - SILVA, Valéria Costa (2019)
This work shows a study about the Etnographic collection Xikrín do Cateté, whichis in the guardo f the Arthur Napoleão Anthropology Laboratory, in Federal University of Pará (UFPA), bringing a little history of the Laboratory, the collection, how it started and his discoverer. Besides that, dealing directly with objects, fotos and documents. From the observation of the difficulties found with the lack of visibility of the laboratory’s collections, information about the etnographic study, this workstarted. Linked to this, na analysis was made of the Museology graduation in the face of paradigm changes. For this, research was done about material culture, and terms like\; colonialism, collection and collecionism; with out forgetting to observe how the Museum of Belém hes be haved with that reality; and how other Museums over come the difficulties of social acceptance of the Indigenous patrimony. Together, we pondered how Museology helped in this construction process, bringing the curricular matrix of the graduation, the old (2009) and the wrrenteone (2012). With this work, I hppe fully expectt hat the visibility of the laboratory and this collection be come better, es well as there sea chesa bout the Indigenous questions, which is very importante as representativity in the North Region.